Isolation of Endophytic Microbes from Gunung Halimun National Park, West Java, Indonesia and Bioassay Their Potency for Eradicating Microbial Crops Pathogen - Sukara, Endang; Melliawati, Ruth (ANNALES BOGORIENSES, 2013)
Gunung Halimun National Park (GHNP) â West Java, Indonesia is the largest preserved primary forest in West Java. Diversity of plants and animals of this park have been studied intensively during the 15 years years. Diversity of endophytic microorganisms, however, has never been reported. Endophytic microbes are those who reside in the interspatial tissues of plants, have a capacity to produce array of secondary metabolites. This paper illustrates the occurrence of endophyte microbes in diverse flowering plants of GHNP. Total of 160 bacteria and 337 fungus were isolated from 86 plants species in the area. Out of that, 159 bacterial isolates and 320 fungus isolates survived in our collection and tested against four major microbial crops pathogen namely Xanthomonas campestris, Pseudomonas solanacearum, Colletotrichum glocosporoides and Fusarium oxysporum cubense. Plate Agar Test Assay method reveals that 51 among 159 bacterial isolates and 62 among 320 endophytic fungal isolates have an ability to inhibit the growth of microbial crop pathogens. Endophytic bacteria can inhibit more microbial crops pathogen but the inhibition ability is less compare to that of endophytic fungi. From our preliminary study clearly shows that endophytic microbes of GHNP should have potential value in developing biological control agent to combat microbial crop pathogens and eventually reduce the use of synthetic chemicals.